Validation of the Chinese version of the resilience scale for the oldest-old - Wang, Ning; Chen, Hongyu; Zhang, Minyi; Wang, Yuanyuan; Xue, Zhihan; Hao, Xixi; Liu, Yan (Frontiers in Psychology, 2023)
Background: Resilience is one of the most important variables associated with adaptive ability. The resilience scale for oldest-old age (RSO) is designed to measure the resilience among oldest-old people. Originally developed in Japan, it has not been used in China. The objective of this study was to translate the RSO into Chinese and investigate its validity and reliability among community oldest-old adults aged ≥80 years. Methods: A total of 473 oldest-old people who come from communities were recruited by convenience sampling for the assessment of construct validity using exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA). In addition, internal consistency reliability, test-retest reliability, face validity and content validity were used to evaluate the psychometric characteristics of RSO Results: The RSO demonstrated good face validity and good content validity. The scale-content validity index of the Chinese version of the RSO was 0.890. Moreover, one factor was extracted by exploratory factor analysis, which accounted for 61.26% of the variance. The RSO had high internal consistency with a Cronbach’s alpha = 0.927. Test-retest reliability was 0.785. item-total correlations were from 0.752 to 0.832. Conclusion: The results of the study indicate that the Chinese version of the RSO questionnaire has good reliability and validity and can be recommended for use by health and social service agencies to assess the resilience of the oldest-old in the community implications for Practice: The validated Chinese version of the RSO is an available and reliable tool for evaluating the resilience of oldest-old Chinese people, suggesting significant clinical application value.